REALISASI WACANA DIALOG DALAM ACARA MATA NAJWA DI TELEVISI TRANS7 (KAJIAN ANALISIS WACANA) - Wenni Elfianita; Agustina Agustina (Faculty of Languages and Arts, Universitas Negeri Padang, 2019)
This research was written to describe (1) the realization of the types of conversation pairs in Mata Najwa dialogue discourse on Trans7 television, (2) the realization of the opportunity to speak in Mata Najwa dialogue discourse on Trans7 television, and (3) the realization of the nature of speech series in Mata Najwa dialogue discourse on Trans7 television. This type of research is a qualitative research with descriptive methods. The findings of this study are as follows: (1) conversational pairs in Mata Najwa Trans7 dialogue discourse are well realized in accordance with the theory used, and found the most types of conversation pairs are fragments of accusations and denials, (2) the opportunity for speech found in discourse Mata Najwa Trans7 dialogue is not in accordance with the theory used in this study, and the turn of the most widely spoken opportunity is seized, and (3) the nature of the speech chain in the Mata Najwa dialogue discourse is also not in accordance with the theory in this study, and the sequence that the most dominant in this event is the chain.